WORD LEVEL EQUIVALENCE OF INDONESIAN–ENGLISH TRANSLATION ABBREVIATION IN THE JAKARTA POST - Kartika Fitri Utami; Sumani Sumani (English Teaching Journal : A Journal of English Literature, Language and Education, 2014)
The objective of the study is to identify the words level equivalence are used by the translator in translating abbreviation found in The Jakarta Post based on the classification of word level equivalence. The researcher applies descriptive qualitative method in carrying out the research. The researcher uses documentation technique. In this study, the researcher uses data source and methodological triangulation. The researcher uses data reduction, data display, and conclusion to analyzing the data. It is in order to describe the fact in The Jakarta Post daily newspaper during February 2012. Some abbreviations were studied. After analyzing the strategies of Indonesian – English translation of abbreviation found in The Jakarta Post, some points can be drawn as follows: (1) translation  by more  general  word  (super ordinate) (because of the  hierarchical  structure of semantic  fields  is  not  language  specific),  (2)  translation  by  more  neutral/less  expressive  word (because the target language has no direct equivalent word), (3) translation using loan or loan word plus explanation (culture specific items, modern concepts and buzz words), (4) translation by paraphrase using related words (when the concept expressed by the source item is lexicalized in the target language but in different form), (5) translation by omission (if the meaning conveyed by certain item or expression is not vital enough), (6) translation by more specific word(subordinate) the target language lacks a super ordinate), and (7) accurate translation (the closest equivalent).